Effect of DNA Aptamer Concentration on the Conductivity of a Water-Gated Al:ZnO Thin-Film Transistor-Based Biosensor - Ogurcovs, Andrejs; Kadiwala, Kevon; Sledevskis, Eriks; Krasovska, Marina; Plaksenkova, Marina; Butanovs, Edgars (MDPI, 2022)
Field-effect transistor-based biosensors (bio-FETs) are promising candidates for the rapid high-sensitivity and high-selectivity sensing of various analytes in healthcare, clinical diagnostics, and the food industry. However, bio-FETs still have several unresolved problems that hinder their technological transfer, such as electrical stability. Therefore, it is important to develop reliable, efficient devices and establish facile electrochemical characterization methods. In this work, we have fabricated a flexible biosensor based on an Al:ZnO thin-film transistor (TFT) gated through an aqueous electrolyte on a polyimide substrate. In addition, we demonstrated techniques for establishing the operating range of such devices. The Al:ZnO-based devices with a channel length/width ratio of 12.35 and a channel thickness of 50 nm were produced at room temperature via magnetron sputtering. These Al:ZnO-based devices exhibited high field-effect mobility (µ = 6.85 cm2/Vs) and threshold voltage (Vth = 654 mV), thus showing promise for application on temperature-sensitive substrates. X-ray photoelectron spectroscopy was used to verify the chemical composition of the deposited films, while the morphological aspects of the films were assessed using scanning electron and atomic force microscopies. The gate–channel electric capacitance of 40 nF/cm2 was determined using electrochemical impedance spectroscopy, while the electrochemical window of the gate–channel system was determined as 1.8 V (from −0.6 V to +1.2 V) using cyclic voltammetry. A deionized water solution of 10 mer (CCC AAG GTC C) DNA aptamer (molar weight −2972.9 g/mol) in a concentration ranging from 1–1000 pM/µL was used as an analyte. An increase in aptamer concentration caused a proportional decrease in the TFT channel conductivity. The techniques demonstrated in this work can be applied to optimize the operating parameters of various semiconductor materials in order to create a universal detection platform for biosensing applications, such as multi-element FET sensor arrays based on various composition nanostructured films, which use advanced neural network signal processing. © 2022 by the authors. Licensee MDPI, Basel, Switzerland.
This research was supported by State Education Development Agency, Project No. 1.1.1.2/ 16/I/001, Research Proposal No. 1.1.1.2/VIAA/4/20/590 “Portable diagnostic device based on a biosensor array of 2D material sensing elements”.
Keywords: Research Subject Categories::NATURAL SCIENCES::Physics; biosensor; DNA; electrochemistry; thin-film transistor; zinc oxide